Notes on the genus Anisomeridium (lichenized Ascomycotina) from Madeira and the Azores (Macaronesia) - Boom, P.p.g. Van Den (Phytotaxa, 2015)
Descriptions are presented for two new species found on Madeira and the Azores: Anisomeridium macaronesicum and A. macropycnidiatum. The differentiation from related species is discussed and a key to the genus Anisomeridium in Macaronesia is added.